2017
DOI: 10.1002/biot.201700064
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterial Substrate‐Mediated Multicellular Spheroid Formation and Their Applications in Tissue Engineering

Abstract: Three-dimentional (3D) multicellular aggregates (spheroids), compared to the traditional 2D monolayer cultured cells, are physiologically more similar to the cells in vivo. So far there are various techniques to generate 3D spheroids. Spheroids obtained from different methods have already been applied to regenerative medicine or cancer research. Among the cell spheroids created by different methods, the substrate-derived spheroids and their forming mechanism are unique. This review focuses on the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 73 publications
1
21
0
Order By: Relevance
“…It is known that, in their natural niche, stem cells divide asymmetrically leading to the formation of 3D clusters and ensuring, at the same time a reservoir of undifferentiated cells and a progeny of committed cells [19]. This has prompted a worldwide effort to develop in vitro models favouring the formation of 3D spheroids either forcing the cells towards cell-to-cell interactions in non-adherent plates or through the development of biomaterial substrates [5,[20][21][22][23][24] demonstrating that in such conditions the stem cells can uniquely maintain features otherwise lost during their culturing [4,25,26]. However, by inducing cell-to-cell interactions non-adherent plates undermine the important role played by the basement membrane of the natural stem cell niche where the important role of proteins such as the laminin in controlling integrin-mediated adhesion and gene expression has clearly been demonstrated [27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…It is known that, in their natural niche, stem cells divide asymmetrically leading to the formation of 3D clusters and ensuring, at the same time a reservoir of undifferentiated cells and a progeny of committed cells [19]. This has prompted a worldwide effort to develop in vitro models favouring the formation of 3D spheroids either forcing the cells towards cell-to-cell interactions in non-adherent plates or through the development of biomaterial substrates [5,[20][21][22][23][24] demonstrating that in such conditions the stem cells can uniquely maintain features otherwise lost during their culturing [4,25,26]. However, by inducing cell-to-cell interactions non-adherent plates undermine the important role played by the basement membrane of the natural stem cell niche where the important role of proteins such as the laminin in controlling integrin-mediated adhesion and gene expression has clearly been demonstrated [27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…[2] Tseng et al summarize the technologies for obtaining multicellular spheroids using biomaterial substrates and their corresponding applications. [3] Tribe et al summarize the potential role of mesenchymal stem cells in the treatment of osteochondral lesions of the ankle. [4] In nine research articles, four papers focus on bone tissue engineering by combining stem cells with electrospun fibers, [5] 3D ceramic scaffolds, [6] and substrates immobilizing cytokines.…”
Section: Shinji Sakai and João F Manomentioning
confidence: 99%
“…Ferreira et al summarize the studies of tumor models combining mesenchymal stem cells and cancer cells . Tseng et al summarize the technologies for obtaining multicellular spheroids using biomaterial substrates and their corresponding applications . Tribe et al summarize the potential role of mesenchymal stem cells in the treatment of osteochondral lesions of the ankle .…”
mentioning
confidence: 99%
“…3D cell constructs, known as cell aggregates or spheroids, can recreate a biomimetic environment inside themselves, and thus, possess some self‐organizing abilities . Therefore, 3D cell constructs are regarded as promising biomaterials for regenerative medicine and pharmaceutical development . It has been reported that cell constructs composed of bone marrow stem cells formed bone‐like mineralized matrices through the endochondral ossification process .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Therefore, 3D cell constructs are regarded as promising biomaterials for regenerative medicine and pharmaceutical development. 11,12 It has been reported that cell constructs composed of bone marrow stem cells formed bone-like mineralized matrices through the endochondral ossification process. 13 It has also been reported that cell interactions and drug sensitivities could be more accurately evaluated for anticancer drug development using cell constructs.…”
Section: Introductionmentioning
confidence: 99%